Cooperative Effects in Catalytic Hydrogenation Regulated by both the Cation and Anion of an Ionic Liquid. Issue 6 (19th December 2012) - Zhu, Wenwen; Yu, Yinyin; Yang, Hanmin; Hua, Li; Qiao, Yunxiang; Zhao, Xiuge; Hou, Zhenshan
Abstract The use of transition‐metal nanoparticles/ionic liquid (IL) as a thermoregulated and recyclable catalytic system for hydrogenation has been investigated under mild conditions. The functionalized ionic liquid was composed of poly(ethylene glycol)‐functionalized alkylimidazolium as the cation and tris(meta‐sulfonatophenyl)phosphine ([P(C6H4‐m‐SO3)3]3−) as the anion. Ethyl acetate was chosen as the thermomorphic solvent to avoid the use of toxic organic solvents. Due to a cooperative effect regulated by both the cation and anion of the ionic liquid, the nanocatalysts displayed distinguished temperature‐dependent phase behavior and excellent catalytic activity and selectivity, coupled with high stability. In the hydrogenation of α, β‐unsaturated aldehydes, the ionic‐liquid‐stabilized palladium and rhodium nanoparticles exhibited higher selectivity for the hydrogenation of the CC bonds than commercially available catalysts (Pd/C and Rh/C). We believe that the anion of the ionic liquid, [P(C6H4‐m‐SO3)3]3−, plays a role in changing the surrounding electronic characteristics of the nanoparticles through its coordination capacity, whereas the poly(ethylene glycol)‐functionalized alkylimidazolium cation is responsible for the thermomorphic properties of the nanocatalyst in ethyl acetate. The present catalytic systems can be employed for the hydrogenation of a wide range of substrates bearing different functional groups. The catalysts could be easily separated from the products by thermoregulated phase separation and efficiently recycled ten times without significant changes in their catalytic activity.